(untitled) (Journal of Health, Population and Nutrition, 2013)
The prevalence of nalidixic acid-resistant Salmonella Typhi (NARST) infection is increasing worldwide. We are reporting an unusual case of infected haematocolpos presenting as urinary obstruction in a patient with fever of unknown origin (FUO). This case report highlights the importance of quinolone-resistant typhoid fever in the differential diagnosis of any acute febrile illness in countries, like India, where Salmonella infection is endemic. DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16833 J HEALTH POPUL NUTR 2013 Sep; 31(3): 403-404